2009
DOI: 10.1002/num.20468
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of nonlinear Schrödinger equation by using time‐space pseudo‐spectral method

Abstract: In this article, a time-space pseudo-spectral method is proposed for the numerical solution of nonlinear Schrödinger equation. The employed method is based on Chebyshev-Gauss-Lobbato quadrature points. Using the pseudo-spectral differentiation matrices the problem is reduced to a system of nonlinear algebraic equations. However, this method is basically a spectral method, but a subdomain-in-time algorithm is used which yields a smaller nonlinear system to study long-time numerical behavior. Because the time-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Of particular interest is GWRM CPU time and memory scaling with N t and N s . Using the case mentioned at the beginning of this section we have performed scans where ∈ [1,15] and ∈ [1,15] . It was found that CPU time scales as 1.0 1.43 and memory usage as 0.0 1.08 (for > 2).…”
Section: Accuracy -The Burger Equationmentioning
confidence: 99%
“…Of particular interest is GWRM CPU time and memory scaling with N t and N s . Using the case mentioned at the beginning of this section we have performed scans where ∈ [1,15] and ∈ [1,15] . It was found that CPU time scales as 1.0 1.43 and memory usage as 0.0 1.08 (for > 2).…”
Section: Accuracy -The Burger Equationmentioning
confidence: 99%
“…More recently Dehghan and Taleei [19] found solutions to the non-linear Schrödinger equation, using a time-space pseudo-spectral method where the basis functions in time and space were constructed as a set of Lagrange interpolants.…”
Section: Generalized Weighted Residual Methodsmentioning
confidence: 99%
“…(4), were solved in the numerical form by means of a pseudospectral method, which was adjusted to the present model, following the lines of works [35] (the application of this method to soliton solutions of equations of the NLS type was recently elaborated in Ref. [36]). The integration domain of variable s, of width T ¼ 40, was sufficient to completely study the shape and dynamics of individual solitons, including those which feature extended ''tails" (simulations of interactions between solitons might require using a larger domain).…”
Section: The Numerical Methodsmentioning
confidence: 99%